DETERMINATION OF THERMAL DIFFUSIVITY OF CEMENT-STABILIZED LATERITE BY TRANSIENT THERMAL FIELD AND INDUCED SURFACE STRESS - AGOUA, EUSÈBE (My University, 2016)
Knowledge of thermo-physical properties of local building materials are necessary for thermal comfort design and construction of residential accommodation. Thermal diffusivity of cement-stabilized laterites were measured under conditions of transient thermal field and induced surface stress, assuming constant temperature within the samples. The laterites were stabilized by 4 %, 8 % and 12 % cement content, and tested at water saturated and unsaturated states. The values of thermal diffusivity of dry and saturated samples were respectively ~ 5.01 x 10-7 m2/s and ~ 5.35 x 10-7 m2/s, and the two values indicated the suitability of stabilized laterite for providing thermal comfort in buildings.
Keywords: Laterite; Cement-stabilization; Thermal diffusivity; Thermal comfort; Constant temperature bath